How Instructional Leadership Influences School Quality: Collaboration in Building School Climate - Supardjoto, Edy; Komariah, Aan; Kurniady, Dedy Achmad; Sururi; Suryadi (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to analyze the influence of instructional leadership on school quality with a focus on efforts to build a school climate through empowerment and persuasion in the implementation of their professionalism. This study used SEM analysis on 162 junior high school teachers in Bandung, West Java Province, Indonesia. By using structural equation modeling, all dimensions of instructional leadership, namely (1) capacity of principal in supporting classroom teaching and student learning, (2) Empowerment and collaborative development of teacher professionalism in a sustainable manner, (3) implementation of vision and mission for school improvement had a positive influence on school climate. Strong positive influence can be seen in all dimensions of school climate on school quality. The direct influence on school quality was obtained from instructional leadership, but it was not significant. Significant influence can be seen in climate on school quality. Instructional leadership and climate simultaneously influence school quality. The school climate was built by principals and teachers through improved learning. Principal can collaborate with teachers through the development of sustainable professionalism and supervision practices for improving the quality of learning.